Sunan Kalijaga Corner : Menghidupkan Nilai Islam Jawa di Perpustakaan UIN Sunan Kalijaga - Jamilah, Asyfiya Qurratal; Zain, Labibah; Pratama, Bagas Aldi (Librarium: Library and Information Science Journal, 2025)
College libraries need to create thematic services to vary the presentation of information to users. This research explores the role of Sunan Kalijaga Corner at UIN Sunan Kalijaga Yogyakarta Library in preserving Javanese Islamic values. Using a case study-based qualitative approach. Data was collected through participatory observation, in-depth interviews, and document analysis. Data analysis uses thematic analysis related to this problem. Test validity with credibility test through extended observation, triangulation, and member check The Corner not only provides rich literature on Javanese Islam, but also becomes a space for education and cultural reflection that encourages religious moderation and an inclusive Islamic identity. The results show that the Corner is able to bridge tradition and modernity through various activities, such as book discussions, workshops, and thematic exhibitions. However, challenges such as limited resources and low interest of the younger generation demand innovative strategies to maintain its relevance and sustainability. This research confirms the importance of Sunan Kalijaga Corner as a model of cultural and religious integration, which strengthens Indonesian Islamic identity amidst the challenges of globalization.